Efficacy and Safety of Chinese Patent Medicine Combined With Oseltamivir in Treatment of Children With Influenza: A meta-Analysis - Duan, Nai-fan; Liu, Bin; Li, Xiao-na; Xiong, Yi-bai; Zhang, Yan; Zhang, Chi; LI, Li; Lu, Cheng; Lyu, Jueni (Frontiers in Pharmacology, 2021)
Background: In recent years, Chinese patent medicines (CPMs) has been widely used for the treatment of children with influenza in China, and has obtained curative effects. Considering that the efficacy and safety of CPMs in the treatment of influenza in children need further evidence evaluation. This meta-analysis aimed to integrate the data from a number of independent studies of the same subject, in order to determine overall treatment trends of children with influenza. Methods: In this meta-analysis, CNKI, Wanfang, SinoMed, PubMed, Cochrane library and Embase were searched of randomized controlled trials (RCTs) published from establishment of the database to December 12, 2020. Two researchers independently extracted data and assessed the methodological quality, and then conducted meta-analysis of the results through Review Manager 5.2. The publication bias was assessed through funnel plot. Results: A total of 21 RCTs and 2960 cases were included. Compared with oseltamivir alone, CPMs combined with oseltamivir reduced the easing time of symptoms, including fever (MD=-0.64, 95% CI [-0.86, -0.41], P<0.00001), cough (MD=-0.82, 95% CI [-1.02, -0.62], P<0.00001), nasal obstruction (MD=-0.88, 95% CI [-1.15, -0.61], P<0.00001) and sore throat (MD=-0.92, 95% CI [-1.26, -0.57], P<0.00001). Meanwhile, combined therapy can also reduce the time of viral shedding (MD=-0.53, 95% CI [-0.70, -0.36], P<0.00001) and can reduce the occurrence of adverse reactions (ADRs) (RR=0.53, 95% CI [0.34,0.83], P=0.005). Conclusions: CPMs combined with oseltamivir can reduce the easing time of symptoms, shorten the time of viral shedding and reduce the number of ADRs. However, due to the obvious heterogeneity and publication bias in the existing research data, these results should be treated with caution. It is necessary to design more rigorous RCTs to verify the effect of CPMs on children with influenza.